2019
DOI: 10.3390/toxins11040206
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Toxin–Antitoxin Systems in Erwinia amylovora Reveals Insights into Diversity and Functional Specificity

Abstract: Toxin–antitoxin (TA) systems are diverse genetic modules with demonstrated roles in plasmid stability, stress management, biofilm formation and antibiotic persistence. However, relatively little is known about their functional significance in plant pathogens. In this study we characterize type II and IV TA systems in the economically important plant pathogen Erwinia amylovora. Hidden Markov Model (HMM) and BLAST-based programs were used to predict the identity and distribution of putative TA systems among sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Previous studies have also reported phylogroup dependent differences in the content of virulence factors ( Baltrus et al, 2012 ; Dillon et al, 2019b ). While it is impossible to speculate the significance of these difference at this point, similar sporadic distribution of TA system linked to genetic similarity has been also described previously both in clinical ( Horesh et al, 2020 ) and plant pathogens ( Shavit et al, 2016 ; Shidore et al, 2019 ).…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Previous studies have also reported phylogroup dependent differences in the content of virulence factors ( Baltrus et al, 2012 ; Dillon et al, 2019b ). While it is impossible to speculate the significance of these difference at this point, similar sporadic distribution of TA system linked to genetic similarity has been also described previously both in clinical ( Horesh et al, 2020 ) and plant pathogens ( Shavit et al, 2016 ; Shidore et al, 2019 ).…”
Section: Discussionsupporting
confidence: 77%
“…Whether all paralogs are active and if they are also functionally diverse is a subject of further research. The parDE and vapBC homologs were also among the most prevalent in another plant pathogen, Erwinia amylovora ( Shidore et al, 2019 ). A vapBC ortholog was characterized as a TA system in the plant pathogen Acidovorax citruli , and was shown to be overexpressed during plant infection ( Shavit et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation